Comparison of traditional strength training and kaatsu strength training on thermal asymmetry, fatigue rate, and peak torque - Barros, N. A.; Aidar, F. J.; Matos, D. G.; Junior, H. A.; Boaretto, S. M.; Souza, R. F.; de Oliveira A. S.; Cercato, L. M.; Camargo, E. A.; Bastos, A. A. (Journal of Exercise Physiology online, 2017)
The aim of this study was to compare variables related to asymmetry, peak torque, and fatigue index in the Traditional strength training method and the Kaatsu strength training method, which is a blood flow restriction training strategy. Ten male subjects with a minimum of 12 months' experience in strength training participated in this study. It was found that while the Kaatsu method resulted in a greater loss of peak torque, its recovery was better at 24 and 48 hrs after the intervention with a higher peak torque peak versus the Traditional method. In addition, it was found that soon after the intervention, the Kaatsu method had a higher fatigue index and a greater asymmetry versus the Traditional method. The findings indicate that the Kaatsu training method promoted an increase in the concentration levels of CK, LDH, and lactate besides presenting higher values of fatigue index, and peak torque.